Protocol for the enhanced management of multimorbid patients with COPD and severe asthma: role of indoor air quality - Emili Vela; Isaac Cano; Josep Roca; Antoni Sisó-Almirall; Carme Hernandez; Ebymar Arismendi; Ramon Farré; Alba Gómez-López; María Figols; Antonio Montilla-Ibarra; Núria Sánchez-Ruano; Benigno Sánchez; et al. (BMJ Open Respiratory Research)
Introduction Reducing unplanned hospital admissions in chronic patients at risk is a key area for action due to the high healthcare and societal burden of the phenomenon. The inconclusive results of preventive strategies in patients with chronic obstructive respiratory disorders and comorbidities are explainable by multifactorial but actionable factors.The current protocol (January 2024–December 2025) relies on the hypothesis that intertwined actions in four dimensions: (1) management change, (2) personalisation of the interventions based on early detection/treatment of acute episodes and enhanced management of comorbidities, (3) mature digital support and (4) comprehensive assessment, can effectively overcome most of the limitations shown by previous preventive strategies. Accordingly, the main objective is to implement a novel integrated care preventive service for enhanced management of these patients, as well as to evaluate its potential for value generation.Methods and analysis At the end of 2024, the specifics of the novel service will be defined through the articulation of its four main components: (1) enhanced lung function testing through oscillometry, (2) continuous monitoring of indoor air quality as a potential triggering factor, (3) digital support with an adaptive case management (ACM) approach and (4) predictive modelling for early identification and management of exacerbations. During 2025, the novel service will be assessed using a Quintuple Aim approach. Moreover, the Consolidated Framework for Implementation Research will be applied to assess the implementation. The service components will be articulated through four sequential 6-month plan-do-study-act cycles. Each cycle involves a targeted cocreation process following a mixed-methods approach with the active participation of patients, health professionals, managers and digital experts.Ethics and dissemination The Ethics Committee for Human Research at Hospital Clinic de Barcelona approved the protocol on 29 June 2023 (HCB/2023/0126). Before any procedure, all patients in the study must sign an informed consent form.Trial registration number NCT06421402.